A study on the stress experience and level of stress among school teachers in Sekolah Menengah Kebangsaan Dato' Sheikh Ahmad, Perlis / Mohd Syawal Rosle, Norafiqahazunah Harun and Nadzirah Mohd Taha - Rosle, Mohd Syawal; Harun, Norafiqahazunah; Mohd Taha, Nadzirah (2010)
The purpose of this study is to identify the level of stress on the factors that influenced to the stress among secondary school's teachers. Researchers distribute the questionnaire to the teachers in Sekolah Menengah Kebangsaan Dato' Sheikh Ahmad, Perlis and out of 35 from 63 teachers are conveniently to answer the questionnaire in that time. From the previous study, the aspects were identified include workload, interpersonal relationship, student's discipline problem and the rules of school.The instrument used in this study is surveying method. Method used in this study is questionnaire form and the sampling has been done by convenience sampling. The data was analyzed using Statistical Package for Social Science (SPSS) version 12.0 for Windows. Descriptive statistic in terms of frequency is used to analyze the level of stress.Results showed that the level of stress among secondary school's teachers were in medium level. The result also showed that there was no relation between the stress factors and marital status. Furthermore, there were relation between workload and gender, teaching experience and age. The most dominant stress' factor was workload.